2013
DOI: 10.1038/npp.2013.178
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Synaptic Cooperation between Cortical and Thalamic Inputs to the Amygdale

Abstract: Fear conditioning, a form of associative learning is thought to involve the induction of an associative long-term potentiation of cortical and thalamic inputs to the lateral amygdala. Here, we show that stimulation of the thalamic input can reinforce a transient form of plasticity (E-LTP) induced by weak stimulation of the cortical inputs. This synaptic cooperation occurs within a time window of 30 min, suggesting that synaptic integration at amygdala synapses can occur within large time windows. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
5
32
0
Order By: Relevance
“…Recent studies also demonstrate that knockout of CB1 specifically localized to glutamatergic terminals facilitates LTP induction at excitatory synapses while deletion of GABAergic CB1 serves to impair induction of this LTP [42]. This if note as the internal capsule BLA CB1 receptor population specifically restricts LTP induction during associative plasticity following coincident activation of both internal and external capsule inputs into the BLA [41]. Thus, the functional impairment of CB1 receptors on BLA glutamatergic terminals by chronic ethanol may ultimately help facilitate the development of ethanol-induced plasticity at these synapses and so contribute to the development of withdrawal-induced anxiogenesis [2, 5].…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also demonstrate that knockout of CB1 specifically localized to glutamatergic terminals facilitates LTP induction at excitatory synapses while deletion of GABAergic CB1 serves to impair induction of this LTP [42]. This if note as the internal capsule BLA CB1 receptor population specifically restricts LTP induction during associative plasticity following coincident activation of both internal and external capsule inputs into the BLA [41]. Thus, the functional impairment of CB1 receptors on BLA glutamatergic terminals by chronic ethanol may ultimately help facilitate the development of ethanol-induced plasticity at these synapses and so contribute to the development of withdrawal-induced anxiogenesis [2, 5].…”
Section: 0 Discussionmentioning
confidence: 99%
“…We have previously demonstrated that chronic ethanol induces dramatic up-regulation of presynaptic function at glutamatergic projections arriving to the BLA from the internal capsule/stria terminalis [5]. These synapses are potently influenced by the eCB system [40, 41]. Within the current experiments, we evaluated CB1-modulation of glutamatergic transmission at this BLA input during both acute and chronic ethanol exposure.…”
Section: 0 Introductionmentioning
confidence: 96%
“…Given that the STC hypothesis is based on the sharing of intracellular PRPs, the cooperative paradigm relies on two assumptions: (a) that weak and strong stimulated synapses belong to two different axonal pools—no presynaptic overlap; and (b) that weak and strong synapses are mapped in the same post‐synaptic neuron—post‐synaptic overlap. Although there is now evidence for single‐cell STC, their original findings, and many others following, had no information regarding the spatial organization of inputs, whether inputs were completely independent or even if inputs co‐terminate in the same neuronal population.…”
Section: Synaptic Tagging and Capture And The Compartmentalization Ofmentioning
confidence: 99%
“…Since the inhibition of CB1R increased competition and considering that competition is determined by a source-to-sink balance, then CB1R inhibition may increase the sink (tag) or decrease the source (PRPs). Although CB1R inhibition is associated with a decrease in protein synthesis, by modulation of the mTOR pathway, the observation that inhibiting CB1R promotes cooperation (Fonseca, 2013), does not support the hypothesis that CB1R inhibition decreases the source. An alternative hypothesis is that inhibition of CB1R increases the sink, which goes in line with CB1R inhibition promoting cooperation.…”
Section: Figure 4 Competition Is Abolished If Prps Availability Is Imentioning
confidence: 85%
“…Indeed, two previous reports have shown that CB1R inhibition downregulates the activity of the mTOR pathway (Busquets- Puighermanal et al, 2013). However, since CB1R inhibition promotes cooperation (Fonseca, 2013), it is highly unlikely that it decreases PRPs synthesis. Also, we did not observe any effect on LTP maintenance, under AM281 application, when the thalamic S2 input was not stimulated.…”
Section: Figure 6 Model Of Synaptic Cooperation and Competitionmentioning
confidence: 98%